Diabetic Neuropathy Patients with Vitamin B12 Deficiency - Alshadood, Ameer K. (University of Thi-Qar Journal of Science, 2022)
Many human deficiencies may be traced back to insufficient levels of vitamin B12, which is soluble in water. Levels of B12 in the blood and a revised demographic study disprove the former hypothesis. Weight, blood levels, and dietary consumption of vitamin B12 were all studied in connection to one another in persons with Type 2 diabetes and diabetic neuropathy. Thirty volunteers were selected from the medical student bodies at the Universities of Kansas and Utah. Initial measurements of height, weight, body mass index, medicines, supplements, age, blood levels of vitamin B12, and dietary intake were collected for a randomised exercise intervention study (Activity for Diabetic Polyneuropathy: ADAPT Study). Nutrition data was entered into a software programme to identify the types and quantities of vitamin B12 ingested during a 3-day period (NDSR), and descriptive statistics were used to profile the individuals. The effects of metformin on patients were compared to those of non-metformin patients using analysis of variance. Blood B12 levels were correlated with demographic variables including age, body mass index, supplement use, and diet by regression analysis. For each set of independent variables at any given moment, a pairwise correlation matrix was compiled. Humans used up an average of 4.3 g of vitamin B12 daily. Taking metformin was not significantly linked to lower blood B12 levels. There was no correlation between age, body mass index, or obesity and vitamin B12 levels in the blood.